Sexual development and reproductive cycle of the Eyespot skate Atlantoraja cyclophora (Regan, 1903) (Chondrichthyes : Rajidae : Arhynchobatinae), in southeastern Brazil - Oddone, Maria Cristina [UNESP]; Norbis, Walter; Mancini, Patricia L.; Amorim, Alberto F. (Inst Oceanografiju I Ribarstvo, 2008)
Specimens of Atlantoraja cyclophora were collected monthly from commercial fishing landings at Guaruja, Sao Paulo State, Brazil, from March 2005 to April 2006 at depths between 10 and 146 m. Males ranged from 13.3 to 58.5 cm TL (n = 396). Both the smallest mature male and the largest immature male were 47.0 cm long. Males' size-at-50% maturity was calculated to be 463 cm. Females ranged from 11.5 to 68.0 cm (n = 401). The smallest mature and the largest immature female were 51.6 and 53. 0 cm long respectively. For the females, size-at-50% maturity was calculated to be 53.2 cm. In the males the hepatosomatic and gonadosomatic indices varied between 0. 48 (August) and 3.54 (November) and between 0. 15 (November) and 1. 45 (June) respectively, with no significant variation for the fourteen-month period. In the females the hepatosomatic and gonadosomatic indices varied from 1. 55 and 6 30 3.54 (both for April 2006) and from 0. 08 (December) to 4.41 (October) respectively, with no significant difference among months. Egg-bearing females were found in all months with proportions varying from 0. 03 (March) to 0. 67 (April). Both males and females undergo an annual cycle, with slight seasonal variations in reproductive activity and a peak in the proportion of egg bearing females between April and July.
Keywords: clasper; elasmobranchs; follicles; egg-bearing; gonads; reproduction; sexual resting period